(untitled) (Research, Society and Development, 2018)
This work aims to highlight books, reading and printed materials used for primary schools in the State of Rio Grande do Norte-Brazil from 1910 to 1930. The research is based in the scientific area of Cultural History and in particular, in the practices and representations, according to Chartier (1990), as well as in the area of History of Reading, by Manguel (1996). The methodology was based on documental research that considered the collection from the Public Archive of the State of Rio Grande do Norte and in the Historical and Geographical Institute of Rio Grande do Norte in Natal-Brazil. As core texts for this analysis the research considered printed textbooks and such as the Cartilha de Ensino Rápido da Leitura by Mariano de Oliveira (1940) and Leituras Potiguares by Antonio Fagundes (1933), the first text book to be adopted in various schools in the State. On one hand, these materials showcase the kind of reading sources used at the time as well as point out the kind of recommendations from the State´s General Direction of Public Instruction, known later on as Board of Education, institutions responsible for reading indications in schools. It is possible to conclude that regarding the literate society, these books, reading and printed material contributed for literacy issues in primary schools.